The Art of Occupation : Crime and Governance in American-Controlled Germany, 1944-1949 - Kehoe, Thomas J., 1980- (Book collections on Project MUSE., 2019)
"Germany has been divided between seemingly irreconcilable assertions of prolonged criminal chaos and narratives of strict martial rule that precluded crime. The Art of Occupation takes a different view on this history, addressing this divergence through an extensive, interdisciplinary analysis of the interaction between military government and social order. Focusing on the American Zone and using previously unexamined American and Germany military reports, court records, and case files, the book assesses crime rates and the psychology surrounding criminality, and thereby offers the first comprehensive exploration of criminality, policing, and the fears amongst Germans and the Americans associated with conquest and potential resistance, social and societal integrity, national future, and a looming threat from communism in an emergent Cold War. It is therefore the fullest study of crime and governance the five years from the first Allied incursions into Germany from the West in September 1944, through the end of the military occupation in 1949. It is an important contribution to American and German social, military and police histories, and historical criminology."